Technical Note on (Q,r,L) Inventory Model with Defective Items - Cheng-Tan Tung (Abstract and Applied Analysis, 2010)
Under a reasonable assumption, we derive an analytical approach that verifies uniqueness of the optimal solution for stochastic inventory models with defective items. Our approach implies a robust method to find the optimal solution.